2022
DOI: 10.1038/s41467-022-32212-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural and dynamic mechanisms of GABAA receptor modulators with opposing activities

Abstract: Abstractγ-Aminobutyric acid type A (GABAA) receptors are pentameric ligand-gated ion channels abundant in the central nervous system and are prolific drug targets for treating anxiety, sleep disorders and epilepsy. Diverse small molecules exert a spectrum of effects on γ-aminobutyric acid type A (GABAA) receptors by acting at the classical benzodiazepine site. They can potentiate the response to GABA, attenuate channel activity, or counteract modulation by other ligands. Structural mechanisms underlying the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 78 publications
3
42
0
Order By: Relevance
“…Mutagenesis and photoaffinity labeling identified a region in the extracellular domain (ECD) at the α+/γ− subunit interface as the location of the high-affinity BZD binding site where mutations often impaired BZD binding or the modulation of GABA-evoked responses [ 34 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] ( Figure 1 A,B). Cryo-EM structures confirmed this as a recognition site for BZDs [ 42 , 44 , 45 , 46 , 47 , 48 ]. The site is homologous to the two GABA binding sites at the β+/α− subunit interfaces, with the ligand binding in a pocket behind loop C, where it interacts with residues from both subunits ( Figure 2 ).…”
Section: Canonical Extracellular High-affinity Binding Sitementioning
confidence: 91%
See 3 more Smart Citations
“…Mutagenesis and photoaffinity labeling identified a region in the extracellular domain (ECD) at the α+/γ− subunit interface as the location of the high-affinity BZD binding site where mutations often impaired BZD binding or the modulation of GABA-evoked responses [ 34 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] ( Figure 1 A,B). Cryo-EM structures confirmed this as a recognition site for BZDs [ 42 , 44 , 45 , 46 , 47 , 48 ]. The site is homologous to the two GABA binding sites at the β+/α− subunit interfaces, with the ligand binding in a pocket behind loop C, where it interacts with residues from both subunits ( Figure 2 ).…”
Section: Canonical Extracellular High-affinity Binding Sitementioning
confidence: 91%
“…The cloning of GABA A R subunits enabled the molecular mechanism of BZD modulation to be probed via mutagenesis, which has led to numerous studies that identified not only the binding site but also the regions contributing to the drug’s modulatory effect. Advances in cryo-electron microscopy (cryo-EM) have recently enabled the resolution of structures of heteromeric GABA A (α1) 2 (βX) 2 (γ2) 1 receptors in complex with BZDs [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Together, these observations aid in the continued search for a complete molecular understanding of the mechanisms of action of BZDs on GABA A Rs.…”
Section: A Brief Historymentioning
confidence: 99%
See 2 more Smart Citations
“… Cys-loop receptor structure and selected binding sites. For each family, a representative dimer is depicted in grey ribbon: GABAAR (8DD2— Zhu et al, 2022 ), GlyR (7M6O— Kumar et al, 2022 ), nAChR (7EKT— Zhao et al, 2021 ), 5-HT3 (6HIO— Polovinkin et al, 2018 ). Ligand bound structures have been superposed to render multiple sites.…”
Section: Cys-loop Receptors Have Cannabinoid Interaction Sitesmentioning
confidence: 99%